Evaluation of a Novel Adjuvanted Vaccine for Ultrashort Regimen Therapy of Artemisia Pollen-Induced Allergic Bronchial Asthma in a Mouse Model - Tabynov, Kairat; Babayeva, Meruert; Nurpeisov, Tair; Fomin, Gleb; Nurpeisov, Temirzhan; Saltabayeva, Ulbossyn; Renu, Sankar; Renukaradhya, Gourapura J.; Petrovsky, Nikolai; Tabynov, Kaissar (Frontiers in Immunology, 2022)
Wormwood (Artemisia) pollen is among the top 10 aeroallergens globally that cause allergic rhinitis and bronchial asthma. Allergen-specific immunotherapy (ASIT) is the gold standard for treating patients with allergic rhinitis, conjunctivitis, and asthma. A significant disadvantage of today’s ASIT methods is the long duration of therapy and multiplicity of allergen administrations. The goal of this study was to undertake a pilot study in mice of a novel ultrashort vaccine immunotherapy regimen incorporating various adjuvants to assess its ability to treat allergic bronchial asthma caused by wormwood pollen. We evaluated in a mouse model of wormwood pollen allergy candidates comprising recombinant Art v 1 wormwood pollen protein formulated with either newer (Advax, Advax-CpG, ISA-51) or more traditional [aluminum hydroxide, squalene water emulsion (SWE)] adjuvants administered by the intramuscular or subcutaneous route vs. intranasal administration of a mucosal vaccine formulation using chitosan-mannose nanoparticle entrapped with Art v 1 protein. The vaccine formulations were administered to previously wormwood pollen-sensitized animals, four times at weekly intervals. Desensitization was determined by measuring decreases in immunoglobulin E (IgE), cellular immunity, ear swelling test, and pathological changes in the lungs of animals after aeroallergen challenge. Art v 1 protein formulation with Advax, Advax-CpG, SWE, or ISA-51 adjuvants induced a significant decrease in both total and Art v 1-specific IgE with a concurrent increase in Art v 1-specific IgG compared to the positive control group. There was a shift in T-cell cytokine secretion toward a Th1 (Advax-CpG, ISA-51, and Advax) or a balanced Th1/Th2 (SWE) pattern. Protection against lung inflammatory reaction after challenge was seen with ISA-51, Advax, and SWE Art v 1 formulations. Overall, the ISA-51-adjuvanted vaccine group induced the largest reduction of allergic ear swelling and protection against type 2 and non-type 2 lung inflammation in challenged animals. This pilot study shows the potential to develop an ultrashort ASIT regimen for wormwood pollen-induced bronchial asthma using appropriately adjuvanted recombinant Art v 1 protein. The data support further preclinical studies with the ultimate goal of advancing this therapy to human clinical trials.